MODELLING NIGERIAN PUBLIC UNIVERSITIES PERFORMANCE THROUGH TOTAL QUALITY MANAGEMENT - Aliyu, Mukhtar Shehu; Abubakar, Mukhtar Salisu; Yakasai, Abubakar Mukhtar; Garba, Abdulkarim (Journal of Applied Structural Equation Modelling, 2018)
The aim of this research is to examine the effects of total quality management on the performance of public universities in Nigeria. University education serves as a means of producing individuals who possess the academic and mental capability, which is expected to help in the production of high-level manpower to the various sectors of the economy. To answer the research questions, one hypothesis is formulated: (a) there is a significant relationship between total quality management and performance of public universities in Nigeria. Data were collected by means of self-administration of a questionnaire completed by academic leaders randomly selected. The questionnaires developed from the prior research were used to measure the total quality management, while performance measurement was based on subjective evaluation involving self-reported measures. The findings revealed that significant relationship exists between total quality management and performance of public universities in Nigeria. The finding of this study would be of relevance to policymakers, such the National Universities Commission (NUC) being the regulator of university education in Nigeria.University Vice Chancellors as administrators can benefit from the study’s outcome. The Tertiary Education Trust Fund (TETFUND) is also a beneficiary of the study finding as it will guide them in resource allocation across the universities. The study recommends that future studies should be conducted on other variables that can predict university performance.